EFFECTIVE PROMOTION STRATEGIES OF JAVAFOODIE IN ATTRACTING INSTAGRAM AUDIENCE - Raniah Destriyani; Siti Fatonah; Isbandi Sutrisno (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2019)
Nowadays social media is very much used by business people in doing business by doing promotions. Instagram is considered as social media that has high potential in offering an item or service. The advantage of promotion through Instagram is that the available range is very wide and unlimited because it uses online facilities. This study examines effective promotion strategies through Instagram social media in attracting audiences that are done by Javafoodie. This study aims to analyze effective promotion strategies by Javafoodie as foodstagram to attract khalayk Instagram. This type of research is descriptive qualitative based on New Media theory. Informants are Javafoodie owners, JavaFood managers and 3 consumers from Javafoodie. Data collection techniques in this study were interviews, observation and documentation. The author conducted a cross check with the informants namely the owner, manager and 3 audiences. In this study, the promotion strategy carried out by Javafoodie has 3 elements, namely information, communication and persuasion. To attract audiences or clients, Javafoodie is good at serving audiences such as replying to messages from audiences quickly, giving rewards and giveaway to clients and audiences to increase cooperation and loyalty. The researcher also found online marketing communication with the use of features (stories, photo uploads, captions, mentions, hastags, geotagging) and visual displays that could attract the attention of the audience. Javafoodie on social media is not only to provide promotional information solely, but also to tell what is given and what is sold. Promotions through Instagram social media are considered effective by Javafoodie as a promotional service for culinary products.